Role of Nasal Endoscopy in Chronic Osteomyelitis of Maxilla and Zygoma: A Case Report - J. S. Arunkumar; Ashok S. Naik; K. C. Prasad; S. G. Santhosh (Case Reports in Medicine)
Osteomyelitis of the jaws was relatively common before the era of antibiotic therapy and preventive and restorative dentistry. Osteomyelitis is an acute or chronic inflammatory process that can involve cortical and trabecular aspects of bone or bone marrow. Cranial bones are infrequently involved, but spreading of inflammation with involvement of surrounding structures represents important risk, such as cerebral abscess, encephalitis, or meningitis. The mandible is more commonly involved than the maxilla. Dentogenic infections cause 38% of mandibular and 25% of maxillary involvement. Involvement of zygoma is very rare. Factors like viral fevers, malnutrition, malaria, anemia,tobacco chewing, immunodeficiency, osteopetrosis, Paget’s disease of bone, and florid cemento-osseous dysplasia (FCOD) result in decreased vascularity of the affected bone, predisposing to the development of osteomyelitis. We present a case of osteomyelitis of left maxilla and zygoma with oroantral fistula in an immunocompetent adult male caused by dentogenic infection. The complete resolution of infection was gained with surgical treatment using nasal endoscope and antibiotic therapy. The aims of this paper are to illustrate diagnostic patterns, to report radiographic findings and surgical treatment using nasal endoscope in a case of osteomyelitis of maxilla and zygoma. The prognosis and cosmetic results are discussed.